Penerapan Paradigma Pedagogi Reflektif dalam Upaya Meningkatkan Kualitas Pendidikan di SMP Strada Marga Mulia Jakarta - Kusmoro, Antonius Happie Susatio Jalu (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2025)
Education is a crucial foundation in building the progress of a nation. The main challenges in education in Indonesia include quality, equity, and relevance to the needs of the times. The reflective pedagogy paradigm emerges as an innovative approach that integrates experience, reflection, and action in learning. This study aims to explore the implementation of this paradigm at SMP Strada Marga Mulia Jakarta to improve the quality of education. Using a descriptive qualitative method, data were collected through observation, in-depth interviews, and document analysis. The focus of the research is to uncover experiences, perceptions, and challenges in implementing this approach. The findings show that the application of the reflective pedagogy paradigm successfully enhanced students' critical thinking, analytical skills, and character. Learning activities involving case studies, simulations, and reflections created an interactive and meaningful learning environment. Students became more active, creative, and capable of linking theory to everyday life practices. However, challenges included teacher readiness, limited time, and resources. SMP Strada Marga Mulia addressed these constraints with regular teacher training, adjustments to the learning schedule, and the provision of supporting facilities. This study concludes that the reflective pedagogy paradigm can be an effective solution to improve the quality of education in Indonesia. With full support from all stakeholders, this approach has the potential to produce a generation that is not only intellectually intelligent but also possesses strong character and the ability to face life's challenges. The experience of SMP Strada Marga Mulia Jakarta can serve as a model for other schools in adopting a similar approach.